Curvature via the de Sitter’s Space-Time - Desideri, Graciela María (Sarajevo Journal of Mathematics, 2024)
We define the central curvature and the total central curvature of a closed curve in a Lorentz $(n + 1)$--space. In addition, we obtain estimates for the total central curvatures of spacelike pure polygons. The study is done by using the n-dimensional de Sitter's space-time. 2000 Mathematics Subject Classification. 53B30, 53C50